EFFECTIVENESS OF SCLERAL CONTACT LENS CORRECTION IN VISUAL REHABILITATION AFTER PENETRATING KERATOPLASTY: A COMPARATIVE STUDY (Modern American Journal of Medical and Health Sciences, 2026)
Purpose. To compare the effectiveness of spectacle and scleral lens correction after penetrating keratoplasty.Materials and methods. A prospective study included 80 eyes. Patients were examined ≥12 months after surgery. Methods included visual acuity, corneal topography, NIBUT, and contrast sensitivity. Statistical analysis included Student’s t-test and Mann–Whitney test.Results. Visual acuity was significantly higher in the scleral lens group. Tear film stability and contrast sensitivity were also improved.Conclusion. Scleral lenses are an effective method of visual rehabilitation after keratoplasty and may be considered the preferred correction option.